MASALAH HUTANG LUAR NEGERI INDONESIA DAN ALTERNATIF SOLUSINYA DALAM PERSPEKTIF KEBIJAKAN EKONOMI MAKRO ISLAM - Muhaimin, Muhaimin (Islamic Economics and Business Faculty of UIN Antasari, 2014)
This paper discusses about economic improvement that can be achieved with the integration amongs of businesses moral reform, state officials and structure changes of efficient economic. Waste and consumer behavior of individual communities and the state officials in preparing the household budget and the state will lead to economic decline. The result of this paper suggests the existence of society and government role especially to reduce the reduce the wasteful spending to create a fair and prosperous society.